Do Religious Ideas Cause Violence?. Issue 1 (2nd January 2019) - Juergensmeyer, Mark
ABSTRACT: Social science seldom takes religion seriously. Graeme Wood shows the folly of this neglect in The Way of the Strangers, his portrayal of the apocalyptic religious ideas held by some of the most ardent ISIS followers. The actions and devotion of members of the Islamic State cannot be understood without grasping what Wood is telling us. Still, a central question remains: Do these religious ideas inevitably lead to violence? Here the jury is still out, since a focus solely on religion, without the socio-political context, can give a skewed perspective on the motives of this violent politico-religious movement.